SPECIFIC RESEARCH OF ORGANIZATIONAL AND ECONOMIC MECHANISM OF MANAGING INDUSTRIAL POLICY IN CURRENT MARKET ECONOMY - Mikhail V. Khachaturyan (Вестник Российского экономического университета имени Г. В. Плеханова)
The article analyzes theoretical and practical models of shaping and developing industrial policy in current market economy. The author explains the forms of managing industrial policy through organizational and economic mechanism and formulates the definition of 'organizational and economic mechanism of managing industrial policy'. He also analyzes the essence, similarity and difference between industrial clusters and territories of leading development as tools of modernizing industrial policy in Russia and overseas. Efficient foreign models of industrial clusters and business chains are investigated. Conclusions about the importance of using the system of industrial zones and clusters for the development of the real sector and industrial potential of economy were formulated.